Community coverage and HIV prevention: assessing metrics for estimating HIV incidence through syringe exchange. - Heimer, Robert (The International journal on drug policy, 2008)
Evaluations of syringe-exchange programme effectiveness that attempt to measure "coverage" by determining the percentage of the at-risk population reached by a programme are insufficient since programmes must provide syringes on a continual basis. Determining the relationship between the extent of programme coverage and its impact (i.e., reductions in disease risk or incidence) is complicated by the lack of controlled trials with cohorts of drug users and instead has to be estimated by imputation, mathematical modelling, or ecological data analysis. This report offers an approach to determine community-wide impact and discusses the limitations of that approach.
Keywords: Chicago; Connecticut; Epidemiologic Methods; Female; Health Services Accessibility; HIV Infections; Humans; Male; Models, Theoretical; Needle-Exchange Programs; Substance Abuse, Intravenous; Syringes